DNSBL for Internet Content Filtering Utilizing pfSense as The Next Generation of Opensource Firewall - Alby A Mugni; Muhammad Herdiansah; Muhammad Andhika; Muhammad Ridwan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
The internet at this time has become an important part of everyday life. From an early age, children already introduced to a digital environment and used to use internet connected devices for various activities such as learning, entertainment, have a chat with family and friends. Apart from convenience and benefits, the Internet also poses a threat to children and adolescents, from inappropriate content such as pornography, violence, narcotics culture, exposure to online pedophiles or dangerous behavior that can make children unsafe. The role of parents in monitoring the online activities of children and adolescents becomes very important. The market offers a variety of control systems for parents who can block or filter content, manage usage, monitor activities, set boundary lines, and quota. This research was conducted to collect basic information about several sites that are often accessed by children with the aim of implementing an internet content screening program utilizing DNSBL and pfSense to increase parental awareness of various technologies that can be used to protect children from the dangers of cyberspace, providing various information for parents of tools that can protect children, and as a form of socialization about the importance of children internet usage monitoring by parents. The study was conducted in the city of Sukabumi by using 30 respondents who were parents of children aged 3-11 years. The most accessible site for children in the city of Sukabumi is Youtube. Therefore, preventive measures are needed to reduce the negative impact caused by filtering content.